Functional Analysis of MAX2 in Phototropins-Mediated Cotyledon Flattening in Arabidopsis - Qing-Ping Zhao; Xiao-Nan Wang; Nan-Nan Li; Zi-Yi Zhu; Shi-Chao Mu; Xiang Zhao; Xiao Zhang (Frontiers in Plant Science, 2018)
Phototropins (phot1 and phot2) are blue-light receptors that control cotyledon flattening and positioning under strong light; however, their functional redundancy restricts our understanding of the specific roles of phot2. To identify the factors responsible for phot2-dependent cotyledon flattening and growth, we screened for light-insensitive mutants among mutagenized phot1 mutants in Arabidopsis thaliana. The double mutant phot1lea1 (leaf expansion associated 1), which is defective in cotyledon flattening and positioning but not the phototropic response was selected. This mutant phenotype could be alleviated by constitutively expressing MORE AXILLARY GROWTH 2 (MAX2), indicating that LEA1 was allelic to MAX2. The max2 mutants (max2-2 and max2-3) are defective in cotyledon flattening, which is similar to that of the phot1 phot2 mutants. Moreover, the amounts of MAX2 transcripts are inhibited in leaves of phot1 mutant. However, the additional disruption of PHOT1 gene in max2-2 or max2-3 did not affect their phenotype, including MAX2-mediated inhibition of hypocotyl elongation. By contrast, phototropins-mediated hypocotyl phototropism was not regulated by MAX2. Together, these results suggest that cotyledon flattening was mediated by both phototropins and MAX2 signaling, but the relationship between two pathways need further study.